Influence of Zr alloying on the mechanical properties, thermal stability and oxidation resistance of Cr–Al–N coatings - Li, W. Z. (2014)
Cr–Al–N coatings with Zr alloying (Zr contents from 0 to 29.5 at.%) were deposited by d.c. reactive magnetron sputtering. The chemical composition and the morphology of as-deposited coatings were characterized, and the phase structure, mechanical properties and wear resistance of the coatings before and after thermal annealing were analyzed and evaluated. With the increase of Zr content, both Cr and N contents decrease whereas Al shows a growing trend. Low Zr (<26.9 at.%) coatings are stoichiometric and present a fcc NaCl-type B1 structure with columnar morphology, while high Zr (≥26.9 at.%) coatings are in N deficiency and have low crystallinity degree. The alloying of low contents of Zr improves the coating hardness and H/E ratio; however, for low ordered coatings these properties decrease significantly. After thermal annealing, fcc structure is kept in low Zr films whereas the crystalline degree is improved in the high Zr ones and their mechanical properties were slightly improved. Two coatings were selected for further testing, representatives of low (CrAlZr5N) and high (CrAlZr27N) Zr contents. The onset oxidation temperature is ∼900 °C and 600 °C for CrAlZr5N and CrAlZr27N coatings, respectively. Mainly Cr2O3 is formed on low Zr coatings whereas mixed oxides of ZrO2 and Cr2O3 are detected on CrAlZr27N sample after thermal exposure. In all tribological tests, low Zr coating presents lower wear rate than the CrAlZr27N coating. In general, the addition of very high Zr contents (>20 at.%) with N deficiency markedly weakens the mechanical properties and the oxidation resistance of Cr–Al–Zr–N coatings.